1995
DOI: 10.1017/s0068245400016294
|View full text |Cite
|
Sign up to set email alerts
|

Excavations at the ancient theatre of Sparta 1992–4: preliminary report

Abstract: Excavations at the Sparta theatre were resumed in 1992: the objective was to survey it and clarify its history. Nine trenches were opened and a catalogue of architectural blocks compiled. A trench in the sw orchestra revealed two staircases; while the seats of honour, the walkway behind, and two or three rows of benches above are preserved, the remainder of the theatre was severely damaged in the 9th–13th centuries. The diazoma's foundations were revealed; below it were ten radial staircases, above seventeen. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Various sites in the Peloponnese have produced distinctive material evidence, such as handmade pottery or coil-made vessels, that has been related generally to Slavic craftsmanship and has been found in association with 'barbarian' weapons and jewellery (Aupert 1980a;1980b;Vryonis 1992;Waywell et al 1995: 451-57;Anagnostakis and Poulou-Papadimitriou 1997;Curta 2001;2010;2016a;2016b;Vionis 2013). Furthermore, artefacts labelled as 'Slavic' (for example, ceramics and metalwork) have been found in territories that were never beyond Byzantine authority and in association with ceramics of the Byzantine artisanal tradition; in Sparta and Corinth these have been interpreted as evidence of a process of 'hellenization' (Sanders in Waywell et al 1995).…”
Section: Archaeological Evidence and Historical Documents: A 'Bilingual' Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…Various sites in the Peloponnese have produced distinctive material evidence, such as handmade pottery or coil-made vessels, that has been related generally to Slavic craftsmanship and has been found in association with 'barbarian' weapons and jewellery (Aupert 1980a;1980b;Vryonis 1992;Waywell et al 1995: 451-57;Anagnostakis and Poulou-Papadimitriou 1997;Curta 2001;2010;2016a;2016b;Vionis 2013). Furthermore, artefacts labelled as 'Slavic' (for example, ceramics and metalwork) have been found in territories that were never beyond Byzantine authority and in association with ceramics of the Byzantine artisanal tradition; in Sparta and Corinth these have been interpreted as evidence of a process of 'hellenization' (Sanders in Waywell et al 1995).…”
Section: Archaeological Evidence and Historical Documents: A 'Bilingual' Approachmentioning
confidence: 99%
“…The traditional historiographic reconstruction of the city, which relies on the Chronicle of Monemvasia, narrates the invasion of Sparta by Slavic tribal and nomadic groups which caused the migration of the inhabitants towards the eastern coast of Laconia, to Mount Parnon or to Sicily (Bon 1951: 31-64). Excavations in the orchestra of the theatre carried out in the 1990s by John Wilkes and Geoffrey Waywell (Waywell et al 1995) and in various areas of the theatre in 2008 by Catherine Morgan, Adamantia Vasilogamvrou and Kalliopi Diamanti (ID879) have uncovered a relevant stratigraphic sequence dated from the eighth to the tenth century. This reveals continuity of Byzantine sociocultural traditions co-existing with a Slavic cultural presence, probably leading to a protracted process of hellenization of the Slavs, as also documented by the aforementioned cemeteries.…”
Section: Archaeological Evidence and Historical Documents: A 'Bilingual' Approachmentioning
confidence: 99%
“…Musti (1996 has suggested that Pausanias's description was an explicit attempt to counter Thucydides, though it is interesting to note that Pausanias has to incorrectly date several monuments in order to make his point (3.14.1). See also Waywell andWilkes 1995. 54.…”
Section: The Struct Ure Of Pausaniasmentioning
confidence: 99%